Uji Efektivitas Mukolitik Ekstrak Umbi Bawang Dayak (Eleutherine bulbosa (Mill) Urb) - Robiatun Rambe; Zulmai Rani; Nur Ain Thomas (State University of Gorontalo, 2021)
Dayak Onions are a typical Borneo plant that have been used by generations of Dayaks as herbal medicine. Empirically, tubers can be used as cough medicines. The purpose of this study was to determine the mucolytic effect of Dayak onion tuber extract by in vitro and the concentration range which gaves an equivalent effect with the effect of 0.1% acetylcysteine. This study conducted extraction using maceration. The test solution was made with a concentration of 0.5%, 1%, and 1.5% mixed with a mucus-phosphate buffer pH 7 20:80. The test solution was incubated for 30 minutes at 37oC. Further, positive control used was 0.1% acetylcysteine drug and the negative control was mucus solution without extract. Viscosity values obtained were analyzed using the One-way Anova statistical test with a confidence level of 99% (α 0.01). Based on the results, it was revealed that the extract of Dayak tuber with a concentration of 0.5%, 1%, and 1.5% showed a significant difference and a concentration of 0.5%. Mucolytic effectiveness was better than positive controls (acetylcysteine).